Forward Guidance at the Zero Lower Bound: Curse and Blessing of Time-Inconsistency - Gregor Böhl; Felix Strobel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Forward guidance as a tool of unconventional monetary policy can be highly efficient to support aggregate demand and to steer the economy out of the zero lower bound (ZLB). However, the effect that stimulates the economy can give rise to a time-inconsistency problem: if the central bank promises to keep interest rates at the ZLB for long, the sub-sequent increase in inflation and economic activity may create a motive for the central bank to forego its promise and to exit the ZLB earlier than announced. We illustrate the time-inconsistency problem in a New Keynesian model with hand-to-mouth consumers. Using a novel and analytically tractable method for handling occasionally binding constraints, we contrast the case of commitment to forward guidance with the case in which monetary policy allows for an early exit of the ZLB. Our method is able to provide results on uniqueness and existence of (ZLB) equilibria. We study the equilibrium selection given different scenarios and conclude that central bankers should be careful when choosing the number of periods with low interest rates in order to avoid the inconsistency problem. Furthermore, we calculate government spending multipliers and argue that the multiplier is even larger if combined with forward guidance.
Keywords: E63; C63; E58; E32; C62; 330; Forward Guidance; zero lower bound; occasionally binding constraints; government spending multiplier